2002
DOI: 10.1136/bmj.324.7333.321
|View full text |Cite
|
Sign up to set email alerts
|

Post-combat syndromes from the Boer war to the Gulf war: a cluster analysis of their nature and attribution

Abstract: Objectives To discover whether post-combat syndromes have existed after modern wars and what relation they bear to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 16 publications
2
76
1
1
Order By: Relevance
“…In the study by Jones et al (2002b), it is significant that cluster analysis did not reveal a gastrointestinal group composed in the main of veterans of the Second World War. Indeed, soldiers diagnosed with non-ulcer dyspepsia were distributed between all three clusters, though to a lesser extent in the neuropsychiatric group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Jones et al (2002b), it is significant that cluster analysis did not reveal a gastrointestinal group composed in the main of veterans of the Second World War. Indeed, soldiers diagnosed with non-ulcer dyspepsia were distributed between all three clusters, though to a lesser extent in the neuropsychiatric group.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the military records of servicemen in the Jones et al (2002b) study revealed that the proportion involved in actual fighting fell over time as numbers in combat-support roles has risen. Of the Boer War veterans, 77% had been in combat, of the First World War pensioners 73.4%, of the Second World War sample 52%, while only 19.8% of the Gulf War sample had seen action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversial syndromes have occurred during and after virtually every major war dating back at least as far as the Crimean War of the 1850s and the US Civil War (Hyams et al 1996;Jones et al 2002). These postulated illnesses have gone by a variety of different names, including Da Costa's syndrome, soldier's heart, shell shock, effort syndrome, neurocirculatory asthenia and battle fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The ravages of war cause more morbidity, disability, and mortality than any disease (Murthy & Lakshminarayana, 2006). In addition to physical injuries associated with military conflicts, psychological consequences have been recognized following all the major wars in the world (Jones et al, 2002). Military organizations in several nations strived to identify barriers to mental care, especially in delineating the potential stigma and cultural differences between Armed Forces (Gould et al, 2010).…”
Section: Background and Significancementioning
confidence: 99%